Using Mass Timber in Multi-Storey and Non-Residential Construction Projects: Motivations and Barriers for Professionals in Quebec - Baptiste Giorgio; Aline Barlet; Pierre Blanchet; Matheus R. Cabral; Cédric Perez; Adrien Gaudelas (BioResources)
Despite their environmental benefits and technical viability, mass timber structures adoption remains limited. As an alternative to steel and concrete in non-residential and multi-storey construction, they represent only 10.2% of buildings four or fewer storeys high, 1% of those five or six storeys high and 4% of those seven to twelve storeys high in Quebec. Based on a purposive sample of 42 interviews with various construction industry professionals in Quebec (Canada), the representation of mass timber construction was highlighted. A thematic analysis approach enabled a study of the motivations and barriers to adopting mass timber and the specific reasons behind them, and to determine whether respondents’ perceptions differ significantly depending on their main professional activity. The results corroborate existing literature while offering deeper insights into motivations and barriers, revealing new viewpoints. Respondents cited construction costs, expertise, manufacturing capacity, regulatory limits, and material specifications as the most critical barriers, while environmental impact and aesthetics of wood as key motivators. The response profile analysis suggests that private developers and general contractors should be the primary targets of measures promoting mass timber adoption. This research will aid in refining policies and strategies to encourage the widespread adoption of mass timber in construction practices.